Cell sheet engineering using the stromal vascular fraction of adipose tissue as a vascularization strategy. (June 2017) - Costa, Marina; Cerqueira, Mariana T.; Santos, Tírcia C.; Sampaio-Marques, Belém; Ludovico, Paula; Marques, Alexandra P.; Pirraco, Rogério P.; Reis, Rui L.
Graphical abstract: Fabrication strategy of highly angiogenic CS, obtained after isolation and culture of SVF from adipose tissue. After 8 days the CS were quite robust and could be detached with the assistance of tweezers and subsequently implanted in vivo after induced hind limb ischemia in mice. Abstract: Current vascularization strategies for Tissue Engineering constructs, in particular cell sheet-based, are limited by time-consuming and expensive endothelial cell isolation and/or by the complexity of using extrinsic growth factors. Herein, we propose an alternative strategy using angiogenic cell sheets (CS) obtained from the stromal vascular fraction (SVF) of adipose tissue that can be incorporated into more complex constructs. Cells from the SVF were cultured in normoxic and hypoxic conditions for up to 8 days in the absence of extrinsic growth factors. Immunocytochemistry against CD31 and CD146 revealed spontaneous organization in capillary-like structures, more complex after hypoxic conditioning. Inhibition of HIF-1α pathway hindered capillary-like structure formation in SVF cells cultured in hypoxia, suggesting a role of HIF-1α. Moreover, hypoxic SVF cells showed a trend for increased secretion of angiogenic factors, which was reflected in increased network formation by endothelial cells cultured on matrigel using that conditioned medium. In vivo implantation of SVF CS in a mouse hind limb ischemia model revealed that hypoxia-conditioned CS led to improved restoration of blood flow. Both in vitro and in vivo data suggest that SVF CS can be used as simple and cost-efficient tools to promote functional vascularization of TE constructs. Statement of Significance: Neovascularization after implantation is a major obstacle for producing clinically viable cell sheet-based tissue engineered constructs. Strategies using endothelial cells and extrinsic angiogenic growth factors are expensive and time consuming and may raise concerns of tumorigenicity. In this manuscript, we describe a simplified approach using angiogenic cell sheets fabricated from the stromal vascular fraction of adipose tissue. The strong angiogenic behavior of these cell sheets, achieved without the use of external growth factors, was further stimulated by low oxygen culture. When implanted in an in vivo model of hind limb ischemia, the angiogenic cell sheets contributed to blood flux recovery. These cell sheets can therefore be used as a straightforward tool to increase the neovascularization of cell sheet-based thick constructs.